RETRACTED: Development of Gene-Pyramid Lines of the Elite Restorer Line, RPHR-1005 Possessing Durable Bacterial Blight and Blast Resistance - Abhilash Kumar, V.; Balachiranjeevi, C. H.; Bhaskar Naik, S.; Rambabu, R.; Rekha, G.; Harika, G.; Hajira, S. K.; Pranathi, K.; Anila, M.; Kousik, M.; Vijay Kumar, S.; Yugander, A.; et al. (Frontiers in Plant Science, 2016)
RPHR-1005, the stable restorer line of the popular medium slender (MS) grain type rice hybrid, DRRH-3 was improved in this study for resistance against bacterial blight (BB) and blast diseases through marker-assisted backcross breeding (MABB). In this study, four major resistance genes (i.e., Xa21 and Xa33 for BB resistance and Pi2 and Pi54 for blast resistance) have been transferred to RPHR-1005 using RPBio Patho-1 (possessing Xa21 + Pi2), RPBio Patho-2 (possessing Xa21 + Pi54) and FBR1-15EM (possessing Xa33) as the donors. Foreground selection was carried out using PCR-based molecular markers specific for the target resistance genes and the major fertility restorer genes, Rf3 and Rf4, while background selection was carried out using a set of parental polymorphic rice SSR markers and backcrossing was continued uptoBC2 generation. At BC2F2, plants possessing the gene combination- Xa21 + Pi2, Xa21 + Pi54 and Xa33 in homozygous condition and with >92% recovery of the recurrent parent genome (RPG) were identified and intercrossed to combine all the four resistance genes. Twenty-two homozygous, pyramid lines of RPHR-1005 comprising of three single-gene containing lines, six 2-gene containing lines, eight 3-gene containing lines, and five 4-gene containing lines were identified among the double intercross lines at F3 generation (DICF3). They were then evaluated for their resistance against BB and blast, fertility restoration ability and for key agro-morphological traits. While single gene containing lines were resistant to either BB or blast, the 2-gene, 3-gene, and 4-gene pyramid lines showed good level of resistance against both and/or either of the two diseases. Most of the 2-gene, 3-gene, and 4-gene containing pyramid lines showed yield levels and other key agro-morphological and grain quality traits comparable to the original recurrent parent and showed complete fertility restoration ability, with a few showing higher yield as compared to RPHR-1005. Further, the experimental hybrids derived by crossing the gene-pyramid lines of RPHR-1005 with APMS6A (the female parent of DRRH-3), showed heterosis levels equivalent to or higher than DRRH-3. The results of present study exemplify the utility of MABB for targeted improvement of multiple traits in hybrid rice.